The Effect of Product Quality and Price Perceptions on Purchase Decisions of Scarlett Body Lotion at Vilshop, Madiun City - Almas Nisaul Fauziah; Supriyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was conducted to analyze and determine the effect of product quality on purchasing decisions for Scarlett Body Lotion at Vilshop, Madiun City. The data analysis technique used is Partial Least squares (PLS). The results showed that product quality had a positive effect on purchasing decisions for Scarlett body lotion at Vilshop, Madiun City, which was acceptable, with a path coefficient of 0.503052 and a T-statistic value of 5.551291 > 1.96 (from table Zα = 0.05) or P-Value 0.000 <0.05, with a significant (positive) result. Then, price perception has a positive effect on purchasing decisions for Scarlett body lotion at Vilshop, Madiun City, with a path coefficient of 0.412970 and a T-statistic value of 4.207986 > 1.96 (from table value Zα = 0.05) or P-value 0.000 <0.05, with significant (positive) results.